Restaging feminisms - Aston, Elaine (Cham, Switzerland Palgrave Macmillan, 2020)
This book offers a re-encounter with the tripartite modelling of liberal, radical, and socialist feminisms foundational to forging feminist approaches to theatre. This lucid account of past-present connections to the staging of feminism assesses the legacies and renewals of all three feminist dynamics as they intersect with austerity Britain, the Weinstein watershed, and the #MeToo movement. Feminist politics, concepts, and the role of affect in the making of political attachments inform an approach that values understanding feminism's past as critical to reanimating and restaging socially progressive, feminist futures. The volume includes case studies of productions staged between 2016 and 2019: Caryl Churchill's Escaped Alone; David Greig's version of The Suppliant Women; Morgan Lloyd Malcolm's Emilia; Nina Raine's Consent; Townsend Theatre's We Are The Lions Mr Manager; and Laura Wade's Home, I'm Darling.
Includes bibliographical references and index.
Keywords: Feminism and theater -- Case studies; Feminism and theater